Usaha Perikanan Tangkap Multi Purpose di Sadeng, Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta - Wahyuningrum, Prihatin Ika; Nurani, Tri Wiji; Rahmi, Tiara Anggia (UNIVERSITAS SRIWIJAYA, 2012)
Sadeng that located in Gunungkidul, Daerah Istimewa Yogyakarta Province, has enough potential fisheries resources. There are relatively new fishing industry activities in Sadeng that began in 2000 by fisherman from Cilacap (Central Java) and fisherman from East Java.Ã‚Â The current research attempts todetermine the aspects of multi-purpose fishing industry that covering technical aspects, marketing aspects, social aspects and financial aspects.Ã‚Â Base on technical aspects, motor ship is one of fishing units that operated in Sadeng.Ã‚Â The productivity of motor ship fishing unit has 1,514.6 kg/trip.Ã‚Â Moreover, marketing aspects, especially for fishing catch marketing, has not been effective due to lack of promotion on fisheries and fishery products.Ã‚Â In addition, financial aspects show the profit of this fishing industry is Rp 55,883,626.67 per year, R/C ratio is 1.18 and Payback Periode is 3.46. Ã‚Â Key words: multi-purpose, technical aspects, marketing aspects, social aspects, financial aspects ABSTRAK Sadeng merupakan salah satu daerah di Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta yang memiliki potensi sumberdaya perikanan yang cukup besar. Usaha perikanan tangkap di Sadeng relatif baru, mulai berkembang pada tahun 2000 dengan didatangkannya nelayan dari Cilacap dan Jawa Timur. Penelitian ini bertujuan untuk mendeskripsikan aspek-aspek yang mempengaruhi usaha perikanan tangkap multi purpose di Sadeng yang meliputi aspek teknik, produktivitas, aspek pemasaran, aspek social dan finansial.Ã‚Â Berdasarkan analisis aspek teknis, salah satu unit penangkapan ikan yang digunakan di Sadeng adalah kapal motor. Produktivitas kapal motor sebesar 1.514,6 kg per trip. Proses pemasaran hasil tangkapan belum berjalan maksimal karena kurangnya promosi kegiatan perikanan dan produk perikanan di Sadeng. Hasil analisis finansial, memperoleh keuntungan sebesar Rp 55.883.626,67 per tahun, R/C 1,18 dan PP 3,46. Ã‚Â Kata kunci: multi purpose, aspek teknis, aspek pemasaran, aspek sosial, aspek finansial